Effect of Peer Promoters on Changes in Adolescent Smoking Knowledge and Attitudes: A School-based Intervention Study - Rachmat, Muhammad; Arif, Nur Arifah; Anwar, Sitti Andriani; Asrianti, Tanti; Awaru, Andi Tenri (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Smoking is currently a trend among youths, with the public emergence of new smokers shifting to this group. Aim:This study aims at analyzing the effect of peer promoters as communicators on the knowledge and smoking attitudes of junior high school adolescents. Methods:The quasi-experimental and non-equivalent control group designs were used. Furthermore, the respondents included 1062 students from two junior high schools in Makassar City, Indonesia, with 473 and 589 males and females, respectively. A total of 801 respondents had paired data (pre and post-test) consisting of 334 in the intervention and 467 in the control school.Paired t-test was used to measure the difference in the pretest and post-test scores of intervention and control schools. Independent t-test was used to determine mean difference between the pretest and post-test scores between intervention and the control schools. Results:The results showed that 18.4% (n = 1062) had smoked, with subtleties of 39.4% male and 1.5% female understudies. the knowledge score increase of 0.82 (p = 0.000) and 0.22 (p = 0.004) was observed in the intervention and control schools, respectively (n = 801). The attitude score also increased by 2.23 (p = 0.080) in the intervention and 2.51 (p = 0.000) in the control school (n = 801). Differences in the knowledge and attitude scores between both schools obtained a value of p = 0.004 and 0.766, respectively. Conclusion: education by peer promoters increase knowledge and change adolescent smoking attitudes indicated the promotion of school-based smoking behavior prevention efforts with intensive peer approach